Producción de textos expositivos con atención al vocabulario académico dentro de una secuencia didáctica ginebrina en un agrupamiento específico de 4º ESO* - Zarraluqui Merchán, Patricia (Huarte de San Juan. Filología y Didáctica de la Lengua, 2018)
In Secondary classrooms, students’ difficulties are usually noted when faced with the academic language. These limitations can condition their success or academic failure, since they will influence the acquisition of knowledge and the adequacy of their productions to the communicative situation, being most of them expository type. To address this problem, it is necessary to undertake the explicit teaching of the vocabulary of this type of language, because it is one of the aspects of academic discourse that has the greatest variability with respect to the conversational language. To this end, a didactic sequence has been put into practice in the form of a project in a specific grouping of 4º ESO, characterized by the variety of origins of the students and their difficulties in learning. The objective was to check whether making an explicit attention to the academic vocabulary, the final product, an infographic about Romanticism literature, improves in its lexical level; and if the place of origin of the students and their mother language influenced the result. The analysis confirmed that its explicit work facilitates their learning and its inclusion in academic expository texts improves their quality.
Keywords: Expository texts; academic vocabulary; vocabulary didactics; project based learning